The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1091/mbc.e09-04-0280
|View full text |Cite
|
Sign up to set email alerts
|

CASK Deletion in Intestinal Epithelia Causes Mislocalization of LIN7C and the DLG1/Scrib Polarity Complex without Affecting Cell Polarity

Abstract: CASK is the mammalian ortholog of LIN2, a component of the LIN2/7/10 protein complex that targets epidermal growth factor receptor (EGFR) to basolateral membranes in Caenorhabditis elegans. A member of the MAGUK family of scaffolding proteins, CASK resides at basolateral membranes in polarized epithelia. Its interaction with LIN7 is evolutionarily conserved. In addition, CASK forms a complex with another MAGUK, the DLG1 tumor suppressor. Although complete knockout of CASK is lethal, the gene is X-linked, enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 58 publications
(73 reference statements)
0
16
0
Order By: Relevance
“…In epithelial cells, for example, some MAGUKs, such as Dlg and ZO-1, are required for the formation of adherens and tight junctions, respectively. In addition to their function as membrane scaffolds (16,21), several MAGUKs also control intracellular protein transport through their ability to bind motor proteins (45,49). Interestingly, some MAGUKs contain specific domains that interact with 4.1 proteins (14,17,18).…”
mentioning
confidence: 99%
“…In epithelial cells, for example, some MAGUKs, such as Dlg and ZO-1, are required for the formation of adherens and tight junctions, respectively. In addition to their function as membrane scaffolds (16,21), several MAGUKs also control intracellular protein transport through their ability to bind motor proteins (45,49). Interestingly, some MAGUKs contain specific domains that interact with 4.1 proteins (14,17,18).…”
mentioning
confidence: 99%
“…Future studies will elucidate the requirements for membrane recruitment of Lin7. In the mouse intestinal epithelium, Lin7C is associated with the baso-lateral membrane, a process that depends on CASK (calcium/calmodulin-dependent serine protein kinase), a scaffolding protein of the MAGUK family (Lozovatsky et al, 2009). Similarly, Lin-7C localization at the baso-lateral surface of Madine Darbine Canine Kidney (MDCK) cells and in renal epithelia requires its interaction with CASK (Straight et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Dlg1 has not been reported to bind directly to cell membranes, and does not contain a membrane localisation domain; instead another factor must be involved in its recruitment to the membrane. It has been reported that the MAGUK protein CASK is involved in Dlg1 localisation to the plasma membrane in some tissues [14,15]. CASK is a multi-domain scaffolding protein with unusual magnesium-independent kinase activity [16], and contains a Hook domain, which mediates interaction with the cytoskeleton and allows for membrane binding [14].…”
Section: Cask Is Required For Dlg1 Membrane Localisation Lumen Formamentioning
confidence: 99%